Image registration for triggered and non‐triggered DTI of the human kidney: Reduced variability of diffusion parameter estimation. Issue 5 (25th June 2014) - Seif, Maryam; Lu, Huanxiang; Boesch, Chris; Reyes, Mauricio; Vermathen, Peter
<x xml:space="preserve">Abstract</x> Background To investigate if non‐rigid image‐registration reduces motion artifacts in triggered and non‐triggered diffusion tensor imaging (DTI) of native kidneys. A secondary aim was to determine, if improvements through registration allow for omitting respiratory‐triggering. Methods Twenty volunteers underwent coronal DTI of the kidneys with nine b‐values (10–700 s/mm2) at 3 Tesla. Image‐registration was performed using a multimodal nonrigid registration algorithm. Data processing yielded the apparent diffusion coefficient (ADC), the contribution of perfusion (FP), and the fractional anisotropy (FA). For comparison of the data stability, the root mean square error (RMSE) of the fitting and the standard deviations within the regions of interest (SDROI) were evaluated. Results RMSEs decreased significantly after registration for triggered and also for non‐triggered scans (P < 0.05). SDROI for ADC, FA, and FP were significantly lower after registration in both medulla and cortex of triggered scans (P < 0.01). Similarly the SDROI of FA and FP decreased significantly in non‐triggered scans after registration (P < 0.05). RMSEs were significantly lower in triggered than in non‐triggered scans, both with and without registration (P < 0.05). Conclusion Respiratory motion correction by registration of individual echo‐planar images leads to clearly reduced signal variations in renal DTI for both triggered and particularly non‐triggered scans. Secondarily, the results suggest that respiratory‐triggering still seems advantageous. J. Magn. Reson. Imaging 2015;41:1228–1235. © 2014 Wiley Periodicals, Inc.